Causes of Divorce among Young Couples: A Phenomenological Study at the Semarang Religious Court - Khatul Ngulya, Fina Mufliq; Sutoyo, Anwar; Japar, Muhammad (Jurnal Bimbingan Konseling, 2022)
Marriage at a young age and lack of preparation are risky to various marriage problems which can lead to divorce. This phenomenological study attempted to describe divorce phenomenon among young couples. Its data were interpreted using a qualitative approach through thematic analysis. Within this analysis, those data were classified into four sub-themes, including: (1) factors which trigger household disharmony among young couples; (2) causes of divorce; (3) efforts made to protect household when there is disapproval from partners; and (4) reasons for filing for divorce. Findings showed that there were various factors that caused divorce among young couples according to mediators’ opinions, selfish, unstable emotion, bad communication, and economy. Meanwhile, the young couples said that they filed for divorce because of abuse, infidelity, and unmet needs. Thus, these findings can give contributions to counselors, extension agents, and social workers, not to mention as a guide to provide pre-marital and post-marital guidance interventions for young couples.